Hurrah Revolutionaries and Polish Patriots: The Polish Communist Movement in Canada, 1918-1950 - Polec, Patryk (Université d'Ottawa / University of Ottawa, 2012)
This thesis constitutes the first full-length study of Polish Communists in Canada, a group that provided a substantial segment of the countries socialist left in the early 20th century. It traces the roots of socialist support in Poland, its transplantation to Canada, the challenges it faced within an ethnic community heavily influenced by Catholicism, the complications caused by its links to the Comintern, and its changing strength and decline. It offers a deeper understanding of the ways in which the Communist party was able to appeal to certain ethnic groups, such as through cultural outreach, as well as its complicated and often arguably counter-productive relationship with the Comintern. It also furnishes important information on the efforts of the RCMP and Polish consulates to maintain control over the communists, as well as how generally improved material conditions among Poles, especially following the Second World War, along with the influence of the Cold War, accounted for a rapid decline in support. The thesis is primarily based on sources generated by the Polish Ministry of Foreign Affairs or, more precisely, by the Polish consulates in Winnipeg, Montreal and Ottawa. One the Canadian side, the thesis took advantage of RCMP records, Canadian security bulletins, immigration records and Polish-language newspapers printed in Canada. By utilizing these sources, this study not only analyses the interaction of the Polish Canadian communist movement with other segments of the Polish community in Canada, but it also moves beyond the introverted approach that has characterized most studies of ethnic organizations in Canada by placing the movement within a “Canadian” context to analyze its relations with the government, broader segments of Canadian society, and the Communist Party of Canada (CPC).
Keywords: labour radicalism; immigration; ethnic Polish; Polonia; Albert Morski; Wladyslaw Dutkiewicz; Polskie Towarzystwo Ludowe; Glos Pracy; Kronika Tygodniowa; Communist Party of Canada